Keeping and cult of the Eucharist in synodal legislation of Poland before the partitions - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2012)
Keeping and cult of the Eucharist un the light of synodal legislation of Poland before historical partitions is an interesting element of religious and cultic life of the faithful clerical and lay people of that historical age. Eucharistic life of the Church, cult of the Eucharist an its keeping is a yardstick and reflection of religious life, it shows the commitment, experiencing and understanding of the truths of faith and this all stimulate for the living according to the faith and commandments. Analysis of resolutions and statutes of Polish legate, provincial and diocesan synods in period before the partitions allows to state, that national Polish culture has character that its Christian throughout. Many synodal resolutions seems to confirm it, indicating the influence of standards of Polish particular law on Polish culture, life and image of the Church. This legislation brought in specific effort so as Christian principles of faith and morality, which strengthened and stimulated taking the Holy Communion, cult of the Eucharist and its keeping struck the roots very into the minds and hearts of the faithful and into the life of Church. Polish synodal legislation is one of the most interesting sources for finding the conditions, in which the Church had lived and acted in Poland. It provides rich material determining and normalizing each sector of religious and church life. The Holy Sacraments were treated in especially rich and detailed manner, including first of all the Eucharist. Synodal legislators gave series of recipes about how to teach and prepare the faithful for Eucharistic life, valid and dignified giving and receiving the Eucharist, its reverence and respect, cult as well as they point out the conditions and purpose to keep the Holy Sacrament. Many times they informed about difficulties and problems connected with Eucharistic life, cult of the Eucharist and taking the Holy Communion, which supposed to shape the life and attitude of real Christian. Especially important were the synodal resolutions after Council of Trent, which were effective tools for post-council revival of the Church, including Eucharistic life. Synodal legislators created and built foundations and roots for our faith, principles of Christian life as well as Christian culture.